OMESTÍVEIS E GORDURA ABDOMINAL DE FRANGOS DE CORTE COBB 500 ® - Pacheco, Natália Grazielle; Galuci, Andréia Fróes; Gottardi, Camila Priscila Fernandes; Souza, Aurélio Ricardo Queiroz; Ferreira, Bruno Reis; Ferreira, Thales Silva (ANAIS DO ENIC, 2018)
-